Upaya Berteologi Kontekstual Dalam Memerangi Penyalahgunaan Narkoba - Putri Yulia Citra Br. Berutu; Friska Deniwaty Pasaribu; Desy Mariana Siringoringo; Fritcen Vanny M Pardede; Elfrida Tampubolon; Ferdinan Majefat; Pirianus Mom (LPPM - STT Kadesi Bogor, 2024)
Drug use is a serious problem that not only impacts individuals personally, but also disrupts social stability and the welfare of society at large. This does not only happen in certain circles, but reaches various levels of society, including teenagers and youth. Factors such as a lack of understanding of the risks, environmental stress, and a lack of social support contribute to worsening the situation. This research aims to analyze the background, causal factors, impacts, and efforts to prevent drug abuse using a theologically based contextual approach. In this research, a qualitative descriptive method was applied by analyzing various literature references. Findings show that drug abuse has a detrimental impact on individuals' physical and mental health, affects social stability, and threatens the future of young people. Prevention efforts involving the role of parents, educational institutions, society and religion are crucial in overcoming this problem. A theologically based contextual approach is also proposed as a strategy that can strengthen understanding of the dangers of drugs and encourage individuals to take a wiser attitude in dealing with them. Thus, this research contributes to increasing understanding of the complexity of drug abuse problems and assists in the development of more effective prevention strategies.